Transmission Electron Microscopic Study on the Spinal Cord of Buffalo Foetii - Kumar, Satender; Gupta, Anuradha; Bansal, Neelam; Pathak, Devendra (Indian Journal of Veterinary Anatomy, 2012)
The present study conducted on spinal cord of 15 buffalo foetii revealed two types of cells viz. the ciliated and non-ciliated cells in 6.4 cm CVRL (57 days) buffalo foetus. A considerable number of gap junctions and the tight junctions were found lying between the ependymal cells. The luminal vesicles or apical cytoplasmic protrusions were present on the ependymal cells in 87.5 cm CVRL (271days) buffalo foetus which suggested the apocrine secretion by ependymal cells.